Ion Channels and Personalized Medicine in Gynecological Cancers - Ana Ramírez; Ingrid Ogonaga-Borja; Brenda Acosta; Andrea Jazmín Chiliquinga; Jaime de la Garza; Patricio Gariglio; Rodolfo Ocádiz-Delgado; Cecilia Bañuelos; Javier Camacho (MDPI AG, 2023)
Targeted therapy against cancer plays a key role in delivering safer and more efficient treatments. In the last decades, ion channels have been studied for their participation in oncogenic processes because their aberrant expression and/or function have been associated with different types of malignancies, including ovarian, cervical, and endometrial cancer. The altered expression or function of several ion channels have been associated with tumor aggressiveness, increased proliferation, migration, invasion, and metastasis of cancer cells and with poor prognosis in gynecological cancer patients. Most ion channels are integral membrane proteins easily accessible by drugs. Interestingly, a plethora of ion channel blockers have demonstrated anticancer activity. Consequently, some ion channels have been proposed as oncogenes, cancer, and prognostic biomarkers, as well as therapeutic targets in gynecological cancers. Here, we review the association of ion channels with the properties of cancer cells in these tumors, which makes them very promising candidates to be exploited in personalized medicine. The detailed analysis of the expression pattern and function of ion channels could help to improve the clinical outcomes in gynecological cancer patients.